Stability Constraints in Optimization of Cracked Columns Subjected to Compressive Follower Load - IMIEŁOWSKI, SZ.; BOGACZ, R. (Engineering Transactions, 2007)
Maximization of the critical force of cracked columns, subjected to generalized follower force is discussed in the paper. The crack is assumed to be formed according to the opening and sliding modes and is modeled by a localized loss of stiffness. Influence of the crack stiffness and its localization on the value of the critical force is analyzed. The optimization process is based on the multimodal approach. The localization of crack with the critical force of the system equal to 137.17 EJ/L2 is found.